Perancangan Mock Up Cetakan Logam Alumunium Bekas Dengan Menggunakan Metode Rekayasa Nilai - Fransiska; Dominikus Budiyarto (Universitas Katolik Musi Charitas, 2020)
The city of Palembang is a city that produces a fairly large amount of waste, especially metal waste which has a total daily waste of 1,358,614 kg / month. Some of this metal waste is stored by the community that will be sold to the trash, but it would be better if this garbage can be processed by the community and made into a product that has a sale value. In this study, researchers designed a mold mock-up tool that could later help make products derived from the metal waste. In this study the authors intend to convert metal waste into key chain products by using a designed mold. After distributing the questionnaire the design pattern data obtained in this study were the shape of the crescent moon, and the dimensions of the size used were 40 mm x 30 mm x 5 mm. Furthermore, researchers conducted several tests using materials from solid soap, researchers also compared the two types of molds, namely open and closed molds. After 10x experiments, the results of closed prints are more effective than open prints, this study uses a value engineering method. The purpose of this research is to be able to make a mock up mold that can later be used as a real mold by using cement material and products that use scrap metal. So that later it will lead to the reduction of metal waste in the city of Palembang.